(untitled) (Journal of Governance and Development (JGD), 2019)
Scholars have identiï¬ed factors like lack of knowledge, lack of effort from the authorities, publicâ€™s attitude, trust issues and exclusion from participation process as the common barriers to effective public participation. The purpose of this study was to examine from the gender context, its impact on the barriers to public participation. An integrated web-based Participatory mapping and text-based survey was administered in Perlis, Malaysia. The results indicate that gender does not inï¬‚uence barrier in public participation for land use planning. Only the results on exclusion from participation process indicate that male have positive impact compared to female respondents. These are important ï¬ndings for developing countries with historically low levels of public participation and low public awareness and knowledge of planning.